Visuoconstructional impairment in Mild Cognitive Impairment: Diagnostic utility and predictive value in the progression to Alzheimer’s disease - Gerardo, Bianca Salguinho (2018)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação